EVALUATION OF IN VITRO ANTIDIABETIC AND ANTIOXIDANT POTENTIAL OF BARLERIA CRISTATA LEAVES EXTRACTS - Vasanth, Sakthivel; Bupesh, Giridharan; Siva Vijayakumar, Tharumasivam; Balachandar, Vellingiri; Rajan Gunasekaran, Durai (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: The objectives of the study were to study the in vitro antidiabetic and antioxidant activity of Barleria cristata leaves extracts. Methods: Ethanol extract and petroleum ether extract of leaf and root of B. cristata were tested for their antidiabetic activity. The in vitro antidiabetic activity from Î±-amylase, Î±-glucosidase, and antioxidant activity was used to assess the potential activity of the fractions. Results: Our attempt results suggest that ethanol and the petroleum ether leaf extract from B. cristata show signs of dose-dependent increases to inhibitory activity on Î±-amylase, Î±-glucosidase enzymes, and antioxidant activity when compared with control. Ethanolic leaves to extract produced maximum in vitro antidiabetic effect and antioxidant activity when compared to petroleum ether extract. Conclusion: The ethanol leaf extract from B. cristata may be used in managing of blood glucose in a medical condition like diabetes.